“TUBULAR GILLS” Extreme gill modification in the Thyasiroidea with the description of Ochetoctena tomasi gen. et sp. nov. (Bivalvia: Thyasiroidea) - Graham Oliver (Zoosystematics and Evolution, 2014)
Three dimensional tubular structures of the ctenidium of some thyasirid bivalves are described for the first time. The classification of the thyasirid gill is modified accordingly into five types based on the number of demibranchs, reflection of the filaments and shape of the filaments, either rod, laminar or tubular. The tubular structure is seen in its most modified form in a chemosymbiotic abyssal species from the south-east Atlantic, which is described here as Ochetoctena tomasi gen et sp. nov.